THE RELATIONSHIP BETWEEN CRM, MARKET ORIENTATION, MARKET TURBULENCE AND MARKETING PERFORMANCE: A REVIEW PAPER - Mastura Roni; Siti Hajar Mohamad (International Journal of Accounting, Finance and Business, 2021)
In the commercial world the importance of retaining existing customers and expanding business is paramount. The costs associated with finding new customers mean that every existing customer could be important. However, the customer relationship management (CRM) platform is still arguable as one of the best customer-centric tools on the market. This review paper aims to develop CRM model for Malaysian Food Manufacturing Industry (FMI). This paper builds ongoing research in manufacturing industries and seeks to place CRM practices in the context of Small and Medium Enterprises (SMEs), which may be particularly suited to market orientation and market turbulence. The implications of the study contribute to combination of resources-based view theory, relationship marketing theory and market orientation theory and provide insights to develop it further. The extensive literature survey a model is put forth for testing.